2005
DOI: 10.1021/jp058098x
|View full text |Cite
|
Sign up to set email alerts
|

On the Probability of Nucleation at the Surface of Freezing Drops

Abstract: Recent publications have proposed that nucleation in the freezing of supercooled drops occurs at the drop surface, an idea supported by statistical thermodynamic arguments by Cahn [J. Chem. Phys. 1977, 66, 3667] coupled with thermodynamic arguments by Tabazadeh et al. [Proc. Natl. Acad. Sci. U.S.A. 2002, 99, 15873]. Whether this phenomenon is general is examined by molecular dynamics simulations of the freezing of deeply supercooled liquid clusters of SeF6. It is found for this model system that while nucleati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…6 The presence of the surfactant could have induced heterogeneous nucleation at the interface with the surfactant. 7 Koop 8 analyzed data on ice nucleation in water droplets in gaseous environments and concluded that the experimental errors associated with the published data are too large to distinguish between surface-and volume-dependent processes on the basis of measured nucleation rates. Laboratory measurements indicate that homogeneous nucleation of ice from pure water droplets is indeed a volumeproportional process for droplet radii above 19 µm.…”
Section: Introductionmentioning
confidence: 99%
“…6 The presence of the surfactant could have induced heterogeneous nucleation at the interface with the surfactant. 7 Koop 8 analyzed data on ice nucleation in water droplets in gaseous environments and concluded that the experimental errors associated with the published data are too large to distinguish between surface-and volume-dependent processes on the basis of measured nucleation rates. Laboratory measurements indicate that homogeneous nucleation of ice from pure water droplets is indeed a volumeproportional process for droplet radii above 19 µm.…”
Section: Introductionmentioning
confidence: 99%
“…surface vs. volume freezing. 1,6,8,[13][14][15][16][17][18] The discussion has found a broad echo in the atmospheric sciences since the phase behavior of aerosols determines weather processes by affecting the energy balance of the atmosphere. On Earth, water and its ices are the obvious focus of interest, but recent high-profile space missions have found other simple molecules, such as ammonia, methane, or ethane, to play a similar role in the atmospheres of certain planets and moons of our solar system (see ref.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that for systems as widely varying as atomic liquids [8], salts [16], tetrahedral liquids [17], hexaflourides [18], metal alloys [7,10], Nickel-Silicon [19], polymers [20], and water [4,21], homogeneous nucleation prefers the liquid-vapor interface, and therefore its rate scales not as volume but rather as area. The mechanism for surface nucleation remains unclear, and even more troubling, its predominance has been qualified and questioned [5,[22][23][24]. Meanwhile, experiments on the nucleation of ice on small particles in supercooled water have revealed a strong enhancement in nucleation rate for particles at the liquid-water -air interface [6,25], suggesting that whatever physics underlies surface nucleation likely extends to heterogeneous nucleation as well.…”
mentioning
confidence: 99%